Community based pedagogy as an eye–opening for pre-service teachers’ initial connections with the school curriculum - Lastra, Sandra Patricia; Acosta, Deyssi; Durán, Norma Constanza (Colombian Applied Linguistics Journal, 2018)
Today more than ever it is critical to guide future teachers in the direction of understanding how people participate and constitute social reality as a seedbed to create more significant language curriculums that respond to school students’ needs and empower them to act more critically in their worlds. This article discusses the way pre-service teachers started to become aware of the need to establish relationships between community resources (linguistic, social, and cultural) and their role as individuals and teachers to enact critical pedagogy. This qualitative exploration was developed with three different groups of students in an English undergraduate program in a public university. Data were gathered by means of community mapping reports (Kreztmann & Mckinght, 1993) and presentations, students’ insights into community based pedagogy in teacher education (Schecter, Solomon, & Kittmer, 2003), and pedagogical projects designed and carried out in the schools where they did the teaching practicum. The outcomes of this study brought to light how pre-service teachers began making connections between the principles of community based pedagogy and the language curriculum in the schools. Findings demonstrate the way they encouraged their students to explore their communities from different perspectives and promoted students’ role of inquirers of themselves and their contexts.